Investigation into oxidation behaviors of cold sprayed Inconel 625 at elevated temperature - Zhou, Shangping (Nanyang Technological University, 2023)
The nickel based IN625 superalloy was exposed to oxidation in laboratory air for 5 hours at 600°C and 800°C respectively. Weight gain measures and Scanning Electron Microscopy (SEM) analytical methods were used to investigate the surface appearance and the oxidation rate. The findings demonstrated that when the temperature rose the rate of oxidation increased. It was proposed that oxygen inward diffusion through the oxide layer and substrate element diffusion in the alloy both affected the rate of oxidation. Chromium and manganese ions moved across the chromia scale constituted a major factor in the oxidation process. In comparison to 800°C, IN 625 gained less weight at 600°C.